Books by Artists - Guest, tim; Celant, Germano; Winnipeg Art Gallery, Winnipeg (Toronto : Art Metropole, 1981)
LeWitt, Sol ; Art & Language ; Hiller, Susan ; Greyson, John ; Knowles, Christopher ; Darboven, Hanne ; Merz, Mario ; Roxler, Martha ; Beuys, Joseph ; Vostell, Wolf ; Maciunas, George ; Abramovic & Ulay ; etc.
Books by Artists, Winnipeg Art Gallery, Winnipeg, May 2 - June 14, 1981 ; National Gallery of Canada / Galerie National du Canada, October 1 - November 1, 1981 ; Norman MacKenzie Art Gallery, November 10 - December 13, 1981 ; Musée d'Art Contemporain, January 8 - February 28, 1982 ; Dalhousie Art Gallery, March 11 - April 18, 1982 ; Emily Carr College of Art, October 4 - October 30, 1982
Engels & Frans
kunstcatalogus